Surface (S) Layer Proteins of Lactobacillus acidophilus Block Virus Infection via DC-SIGN Interaction - Prado Acosta, Mariano; Geoghegan, Eileen M.; Lepenies, Bernd; Ruzal, Sandra; Kielian, Margaret; Martinez, Maria Guadalupe (Frontiers in Microbiology, 2019)
Alphaviruses and flaviviruses are important human pathogens that include Chikungunya, Dengue and Zika virus, which can cause diseases in humans ranging from arthralgia to hemorrhagic fevers and microcephaly. It was previously shown that treatment with Surface (S) layer protein, present on the bacterial cell-envelope of Lactobacillus acidophilus, is able to inhibit viral and bacterial infections by blocking the pathogen’s interaction with DC-SIGN, a trans-membrane protein that is a C-type calcium-dependent lectin. DC-SIGN is known to act an attachment factor for several viruses including alphaviruses and flaviviruses. In the present work we used alphaviruses and flaviviruses as a model system to dissect the mechanism of S-layer inhibition. To evaluate the protective effect of S-layer in DC-SIGN-expressing cells, we used 3T3 cells, either WT or stably expressing DC-SIGN, and we tested the alphaviruses Semliki Forest virus and Chikungunya virus and the flaviviruses Zika virus and Dengue virus. DC-SIGN expression significantly enhanced infection by all four viruses. Treatment of the cells with S-layer prior to infection decreased virus infectivity only in cells expressing DC-SIGN. Using confocal microscopy and flow cytometry we showed that S-layer binding to the cells was independent of DC-SIGN expression. However, S-protein only prevented Semliki Forest virus adsorption and internalization in DC-SIGN-expressing cells and had no effect on virus binding to DC-SIGN-negative cells. Inhibition of virus binding occurred in a time dependent manner, with a significant reduction of infection requiring at least a 30 minute pre-incubation of S-layer with DC-SIGN-expressing cells. These results suggest that S-layer has a different mechanism of action compared to mannan, a common DC-sign binding compound that has an immediate effect in blocking viral infection. This difference could reflect slower kinetics of S-layer binding to the DC-sign present at the plasma membrane. Alternatively, the S-layer/DC-SIGN interaction may trigger the activation of signaling pathways that are required for the inhibition of viral infection. Together our results add important information relevant to the potential use of Lactobacillus acidophilus as an antiviral therapy.